Effects of selected bioactive food compounds on human white adipocyte function. Issue 1 (December 2016) - Björk, Christel; Wilhelm, Uta; Mandrup, Susanne; Larsen, Bjørk; Bordoni, Alessandra; Hedén, Per; Rydén, Mikael; Arner, Peter; Laurencikiene, Jurga
Abstract Background Previous studies suggest that intake of specific bioactive compounds may have beneficial clinical effects on adipose tissue partly due to their anti-inflammatory and insulin-sensitizing properties. With the overall aim to contribute to better understanding of the mechanisms of selected bioactive nutrients on fat metabolism, we investigated their role on human white adipocyte function. Methods The influence of the omega-3-fatty acid docosahexaenoic acid (DHA), the anthocyanin (AC) cyanidin-3-glucoside and its metabolite protocatechuic acid, and the beta-glucan metabolite propionic acid (PI) on adipokine secretion, fatty acid metabolism (lipolysis/lipogenesis) and adipocyte differentiation (lipid accumulation) was studied in human fat cells differentiated in vitro. To investigate possible synergistic, additive or antagonistic effects, DHA was also combined with AC or PI. Results Each compound, alone or together with DHA, suppressed basal adipocyte lipolysis compared to control treated cells. DHA alone attenuated the secretion of pro-inflammatory adipokines such as chemerin, interleukin-6 (IL-6) and monocyte chemoattractant protein-1 (MCP-1/CCL2 ), whereas AC suppressed only the latter two. Treatment with PI decreased IL-6, tumour necrosis factor alpha (TNFα) and adiponectin secretion. A combination of DHA and AC decreased TNFα secretion and increased insulin-stimulated lipogenesis. No effect was found on adipocyte differentiation. At the selected concentrations, none of the compounds was found to be cytotoxic. Conclusion The studied bioactive food compounds or their metabolites have beneficial effects in human primary fat cells measured as decreased basal lipolytic activity and secretion of inflammatory markers. A minor effect was also observed on insulin-stimulated glucose uptake albeit only with the combination of DHA and AC. Taken together, our results may link the reported health benefits of the selected bioactives on metabolic disorders such as insulin resistance, hypertension and dyslipidemia to effects on white adipocytes.